Risk factors for ulcerative colitis in children - N.Yu. Bukulova (Zaslavsky O.Yu., 2020)
Background. Inflammatory bowel disease is one of the pressing problems in pediatric gastroenterology, due to the rapid spread of this pathology, displacement in the onset of the disease at an early age of a child (the first three years of life), the formation of severe complications, low efficiency of modern treatment regimens. The problem of ulcerative colitis in children requires further comprehensive study, including risk factors of the emergence of disease that will enable the formation of risk groups for the development of the disease, rationale for the preventive measures for the notification. Materials and methods. Study of risk factors was conducted by interviewing 100 mothers whose children suffered from ulcerative colitis. The control group consisted of 30 mothers of healthy children. Results. Based on mathematical analysis of biomedical risk factors for the development for ulcerative colitis in children, the most significant are identified as follows: burdened heredity for diseases of the digestive system, intestinal dysfunctions at an early age, repeated courses of antibiotic therapy, secondary lactase deficiency, frequent respiratory diseases. The algorithm was developed for predicting ulcerative colitis in childhood as well as the well-grounded approaches to the prevention of this pathology.